ANALYSIS OF MEANS OF REGISTRATION OF INFORMATION IN SYSTEMS MANAGEMENT - Davletyants , O. I.; Naida , O. M. (Problems of Informatization and Management, 2021)
ANALYSIS OF MEANS OF REGISTRATION OF INFORMATION IN SYSTEMS MANAGEMENT